1998
DOI: 10.1074/jbc.273.17.10696
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Regulates Transcription of the p21 Cyclindependent Kinase Inhibitor Gene through Sp1 and CBP/p300

Abstract: Progesterone has biphasic effects on proliferation of breast cancer cells; it stimulates growth in the first cell cycle, then arrests cells at G 1 /S of the second cycle accompanied by up-regulation of the cyclin-dependent kinase inhibitor, p21. We now show that progesterone regulates transcription of the p21 promoter by an unusual mechanism. This promoter lacks a canonical progesterone response element. Instead, progesterone receptors (PRs) interact with the promoter through the transcription factor Sp1 at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
231
3
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 342 publications
(260 citation statements)
references
References 36 publications
15
231
3
1
Order By: Relevance
“…Similarly, induction of p21 during keratinocyte di erentiation or by progesterone is dependent on spacing of the promoter elements. Insertions between responsive elements or placing of the responsive elements too close to the transcription initiation site abolish the transcriptional activation of p21 (Owen et al, 1998;Prowse et al, 1997). Here, a mutant construct a ecting the TbRE but not eliminating any of the Sp1-binding sites (mut 2.3) (Datto et al, 1995b), showed a weaker induction of luciferase activity by Ras similarly to the mutants a ecting the Sp1-binding site 2 and TbRE simultaneously (mut 2 and mut 2.2).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Similarly, induction of p21 during keratinocyte di erentiation or by progesterone is dependent on spacing of the promoter elements. Insertions between responsive elements or placing of the responsive elements too close to the transcription initiation site abolish the transcriptional activation of p21 (Owen et al, 1998;Prowse et al, 1997). Here, a mutant construct a ecting the TbRE but not eliminating any of the Sp1-binding sites (mut 2.3) (Datto et al, 1995b), showed a weaker induction of luciferase activity by Ras similarly to the mutants a ecting the Sp1-binding site 2 and TbRE simultaneously (mut 2 and mut 2.2).…”
Section: Discussionmentioning
confidence: 78%
“…Besides p53, transcription factor Ap-2 (Zeng et al, 1997), E2F-1/DP-1 complex (Hiyama et al, 1997), E2A (Prabhu et al, 1997), an ets-oncogene related E1AF (Funaoka et al, 1997), C/EBP , RAR (Liu et al, 1996a), VDR (Liu et al, 1996b), STATs (Chin et al, 1996), and Sp1 family (Biggs et al, 1996;Li et al, 1998;Owen et al, 1998;Prowse et al, 1997;Yan and Zi , 1997) are known to stimulate p21 promoter activity. Our results show that Ras induces p21 transcriptionally and that the Ras-responsive region in p21 promoter spans a short region downstream of the nucleotide 7110 relative to the transcription start site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with this idea, the promoter region of the Bmf gene possesses . [31][32][33] Like most promoter activities, this may reflect the fact that FK228-mediated Bmf transcription can be activated depending upon these multiple promoter activities. This may at least partially explain why FK228 or CBHA activates Bmf expression differently in different cells, since these promoter activity may differ depending upon cell types.…”
Section: Discussionmentioning
confidence: 99%